Identification of Predictive CT Angiographic Factors in the Development of High-Risk Type 2 Endoleaks after Endovascular Aneurysm Repair in Patients with Infrarenal Aortic Aneurysms - Löwenthal, D.; Herzog, L.; Rogits, B.; Bulla, K.; Weston, S.; Meyer, F.; Halloul, Z.; Pech, M.; Ricke, J.; Dudeck, O. (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2015)
Purpose: An extensive analysis of the value of computed tomography (CT) parameters as potential predictors of the clinical outcome of type 2 endoleaks after endovascular aortic aneurysm repair (EVAR).Materials and Methods: Initial CT scans of 130 patients with abdominal aortic aneurysms (AAAs) were retrospectively reviewed. On the basis of postoperative CT scans and angiographies, patients were stratified into a low-risk group (LRG; without or transient type 2 endoleak; n = 80) and a high-risk group (HRG, persistent type 2 endoleak or need for reintervention; n = 50). Statistical analysis comprised a univariate and multivariate analysis.Results: Anatomical, thrombus-specific, as well as aortic side branch parameters were assessed on the initial CT scan. Of all anatomical parameters, the diameter of the immediate infrarenal aorta was significantly different in the univariate analysis (LRG 22.4 ± 3.8 mm; HRG 23.6 ± 2.5 mm; p = 0.03). The investigation of the thrombus-specific parameters showed a trend towards statistical significance for the relative thrombus load (LRG 31.7 ± 18.0 %; HRG 25.3 ± 17.5 %; p = 0.09). Assessment of aortic side branches revealed only for the univariate analysis significant differences in the patency of the inferior mesenteric artery (LRG 71.3 %; HRG 92.0 %; p = 0.003) and their diameter (LRG 3.3 ± 0.7 mm; HRG 3.8 ± 0.9 mm; p = 0.004). In contrast, the number of lumbar arteries (LAs; LRG 2.7 ± 1.4; HRG 3.6 ± 1.2; univariate: p = 0.01; multivariate: p = 0.006) as well as their diameter (LRG 2.1 ± 0.4 mm; HRG 2.4 ± 0.4 mm; univariate: p < 0.001; multivariate: p = 0.006) were highly significantly associated with the development of type 2 endoleaks of the HRG.Conclusion: The most important predictive factors for the development of high-risk type 2 endoleaks were mainly the number and the diameter of the LAs which perfused the AAA.Key Points:• This study is a very detailed and comprehensive analysis of the value of various CT parameters as potential predictors of the clinical outcome of type 2 endoleaks after EVAR.• Anatomical as well as thrombus-specific parameters were unsuitable as predictors.• The most important predictive factors were mainly the number and the diameter of the LAs which perfused the AAA.Citation Format:• Löwenthal D., Herzog L., Rogits B. et al. Identification of Predictive CT Angiographic Factors in the Development of High-Risk Type 2 Endoleaks after Endovascular Aneurysm Repair in Patients with Infrarenal Aortic Aneurysms. Fortschr Röntgenstr 2015; 187: 49 – 55
Keywords: aorta; CT angiography; aneurysm